Soil and Carbon Conservation for Climate Change Mitigation and Enhancing Sustainability of Agricultural Development - Agus, Fahmuddin (Pengembangan Inovasi Pertanian, 2013)
Agricultural sector is a sector which is vulnerable to climate change and a source of greenhouse gas (GHG) emissions. Therefore, besides the need for adaptation, agriculture has a potential to mitigate the climate change.  This paper discusses the adaptation and mitigation of agriculture to the changing climate through soil and carbon conservation. Various soil conservation technological  innovations on mineral soils potentially increase carbon stocks and subsequently improve soil physical and chemical properties and activities of living soil organisms. Conservation of peat soil basically reduces the rate of decomposition of organic matter or GHG emissions and also prolongs the lifespan of the peat. Soil and carbon conservation  aimed to answer a variety of local issues such as sustainable agriculture and global issues such as reduction of GHG emissions from agricultural land. Rehabilitation of degraded peat shrub and peat grassland  to agricultural land potentially provides significant carbon conservation and economic benefits. Evaluation of  land status, land suitability, technology readiness, financial and institutional supports are the prerequisites needed to rehabilitate the abandoned     land into productive and higher carbon storage lands.